The Implied Jump Risk of LIBOR Rates - LIM, Kian Guan (Institutional Knowledge at Singapore Management University, 2005)
This paper examines implied parameters from options on LIBOR futures. Jump-diffusion models are found to offer superior in-sample and out-of-sample performance when compared to their pure diffusion counterpart. The need to incorporate stochastic jump magnitudes into LIBOR dynamics is also documented. In addition, empirical evidence reveals that the jump component in LIBOR rates is important for pricing their derivatives. Furthermore, variation in jump risk often coincides with Federal Open Market Committee (FOMC) decisions and a small subset of macroeconomic announcements.